Species composition of birds from the Cat Tien national park, Dong Nai province - Tuong, Ngo Xuan; La, Truong Van (Academia Journal of Biology, 2006)
A total of 348 bird species belonging to 64 families, 18 orders were recorded in the Cat Tien national park, Dong Nai province. The Passeriformes order is the most divers order with 27 families (42.19% of the order number of this park), 169 species (48.56%). Among 348 bird species recorded in the Cattien national park, 29 species are listed in the Governmental Decree No 48/2002/ND-CP (2002), 22 species in the Red Data Book of Vietnam (2000) and 16 species in the IUCN Red List (2003); 4 species are endemic of Vietnam. The individual numbers of several threatened species (E.g. Polyplectron germaini Elliot, 1866; Arborophila charltoni Delacour, 1927; Arborophila davidi Delacour, 1927; Pavo muticus Delacour, 1949; Ciconia episcopus (Boddaert, 1783)...) are still abundant; especially, the orange-necked partridge (Arborophila davidi Delacour, 1927), an endemic species of Vietnam, just now is recorded only in the Cat Tien national park.